Design paradigm and syntagm of woven bamboo packaging (besek) - Sutrisno, Andika Agung; Sunarto, Bambang; Dharsono, Dharsono (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Communication becomes a powerful means of cultural diffusion and an alternative choice for the community. Recently, modern society has been observed to be highly consumeristic, where the image becomes a consideration in the decision-making to purchase. Visual design on the packaging has an effect on consumers' purchasing decisions. The traditional woven bamboo packaging (besek) has an exciting phenomenon in modern society today (urban). The qualitative approach was used with narrative construction or textual descriptions of phenomena. Formal analysis and sign interpretation were used to answer research problems. The formal analytical method was used to identify the way syntagmatic shapes produce paradigms in meaning. The alternative modern packaging that follows the recent developments does not significantly replace the presence of besek as a medium to come to the collective memory of the target audience. Besek is a small part of existing past cultural products that compete with the modern packaging paradigm. Every past cultural product that successfully maintains its existence enables the establishment of an image and becomes a bridge to collective memory in the contemporary era